Shackleton Memorial Library, Scott Polar Research Institute, Cambridge England - Campbell, Sandy (2022)
The Shackleton Memorial Library is part of the larger library of the Scott Polar Research Institute. These doors lead into a "friends room" which contains displays and a meeting area.